Experimental Study on Sedimentary Rock’s Dynamic Characteristics under Creep State Using a New Type of Testing Equipment - Wanpeng Huang; Wenbin Xing; Shaojie Chen; Yang Liu; Kai Wu (Advances in Materials Science and Engineering)
Under high stress, rock in the creep state is vulnerable to external impact load, causing the irreversible perturbation deformation of rock or even sudden failure. To explore the dynamic characteristics of sedimentary rock in the creep state, a siltstone specimen was experimentally studied using a new type of experimental system for rock creep perturbation. Compared to the currently available equipment for studying rock dynamics, this new type of experimental system provides a long-term and stable high static stress to maintain the creep state of rock specimen. This is independent of power supply because it provides static stress by gravity load. Moreover, the equipment provides a dynamic impact load through the free fall of impact weights. This study shows that the perturbation deformation of sedimentary rock increased in two stages: decay phase and sustained development phase. When the static stress reached up to ~85% of the rock’s ultimate strength and the axial strain reached up to 80% of the ultimate failure strain, the rock became sensitive to impact load. This static stress level is basically the same as its long-term strength. With increasing impact strength, the increment curve of the rock creep perturbation deformation was transformed from the decay phase to the sustained development phase in advance, making the rock sensitive to external perturbation at a low static loading stress level.